Incidence and risk factors of polycystic ovary syndrome among women in reproductive age group attending a tertiary health care hospital in Western Maharashtra - Shinde, Khushboo Suresh; Patil, Sunil Somnath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Polycystic Ovary Syndrome (PCOS) is an endocrine disorder affecting women of reproductive age group. Though its incidence is markedly increasing, the awareness is still low; as a result it remains undiagnosed. Aim of this study was to find the incidence and risk factors of PCOS among women in reproductive age group, so as to encourage young women to seek timely treatment and prevent its long term complications. Methods: A study was conducted over a period of 1 year amongst 100 women attending the Gynecology OPD using a paper based questionnaire. General examination and the required laboratory tests were done to confirm the diagnosis. Results: It was found that the incidence of PCOS among the study population was 21%. Risk factors include lack of physical activity, irregular menstrual cycle, body mass index more than 25, and Waist-hip ratio above 0.86. Conclusions: It is seen that there is a need to educate women at an early stage to prevent the development of this syndrome and its early detection by them. This will facilitate the health professionals to start the treatment at a stage where the complications have not yet set in.